2012
DOI: 10.1016/j.jss.2011.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Empirical findings on team size and productivity in software development

Abstract: The size of software project teams has been considered to be a driver of project productivity. Although there is a large literature on this, new publicly available software repositories allow us to empirically perform further research. In this paper we analyse the relationships between productivity, team size and other project variables using the International Software Benchmarking Standards Group (ISBSG) repository. To do so, we apply statistical and machine learning approaches to a preprocessed subset of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 28 publications
3
65
0
Order By: Relevance
“…Also, since the two observed teams exhibit characteristics in terms of size and roles similar to others reported in the research literature, e.g. [24], [25], we believe that the impact of the single company is not a substantial limitation.…”
Section: E Threatssupporting
confidence: 75%
See 1 more Smart Citation
“…Also, since the two observed teams exhibit characteristics in terms of size and roles similar to others reported in the research literature, e.g. [24], [25], we believe that the impact of the single company is not a substantial limitation.…”
Section: E Threatssupporting
confidence: 75%
“…These roles are a subset of the fairly extensive stakeholder roles identified by Acuna et al [23] and Yilmaz et al [24]. The size of the teams, 13 and 16, is comparable to other software development teams in industry as reported by [25] and [26]. Except for one of the line managers and some software testers, all members of each team shared an office space.…”
Section: A Team Structure and Subjectsmentioning
confidence: 69%
“…Putnam sampled 491 projects and concluded that productivity is higher for smaller teams with an optimal group size of 3-5 staff [161]. The rule of thumb [92] -teams of 9 or more are significantly less productive than smaller teams -defines another empirical threshold which is supported by studies like [85] and [166].…”
Section: More Useful Discoveriesmentioning
confidence: 99%
“…Individuals use metaphors to help explain their intuition to themselves and to share it with others, since metaphors involve the transfer of information from a relatively familiar domain. Rodríguez et al (2012) analyse the relationships between productivity, team size and other project variables using the International Software Benchmarking Standards Group repository. The results showed that there are statistical correlations between team size, effort, productivity and project duration; however, these correlations are not always what one would expect from the literature or intuition.…”
Section: Intuition In Project Managementmentioning
confidence: 99%